Phototransistors with Negative or Ambipolar Photoresponse Based on As‐Grown Heterostructures of Single‐Walled Carbon Nanotube and MoS2. (12th August 2018) - Nguyen, Van Tu; Yim, Woongbin; Park, Sae June; Son, Byung Hee; Kim, Young Chul; Cao, Thi Thanh; Sim, Yumin; Moon, Yoon‐Jong; Nguyen, Van Chuc; Seong, Maeng‐Je; Kim, Sun‐Kyung; Ahn, Yeong Hwan; et al.
Abstract: A facile synthesis method for the heterostructures of single‐walled carbon nanotubes (SWCNTs) and few‐layer MoS2 is reported. The heterostructures are realized by in situ chemical vapor deposition of MoS2 on individual SWCNTs. Field effect transistors based on the heterostructures display different transfer characteristics depending on the formation of MoS2 conduction channels along SWCNTs. Under light illumination, negative photoresponse originating from charge transfer from MoS2 to SWCNT is observed while positive photoresponse is observed in MoS2 conduction channels, leading to ambipolar photoresponse in devices with both SWCNT and MoS2 channels. The heterostructure phototransistor, for negative photoresponse, exhibits high responsivity (100–1000 AW −1 ) at low bias voltages (0.1 V) in the visible spectrum (500–700 nm) by combining high mobility conduction channel (SWCNT) with efficient light absorber (MoS2 ). Abstract : Heterostructures of single‐walled carbon nanotubes (SWCNT) and MoS2 are synthesized by chemical vapor deposition. Negative or ambipolar transfer characteristics are observed depending on the formation of MoS2 channels along SWCNTs. Negative photoresponse due to electron transfer from MoS2 to SWCNT exhibits higher responsivity and faster response due to the high mobility of SWCNT and efficient light absorption by MoS2 .